Producción de biodiesel a partir de aceite de palma en un reactor de lecho fijo con metóxido de calcio como catalizador (2014)
ABSTRACT: In this research, the behavior of calcium methoxide as catalyst for the production of biodiesel from palm oil in a continuous system was studied. Initially, operating conditions such as CaO activation temperature (25°C), reaction temperature (60°C) and molar ratio methanol-oil (10)were established for a batch reactor. Then, the schematic diagram of the experimental setup and its implementation were described for a packedbed laboratory scale reactor with continuous flow; for this system, yields of methyl esters of 20% with a residence time of 60 min were obtained. The use of co-solvent such as tert-Bbutanol and ethyl acetate in the continuous reaction system was also investigated, aiming to eliminate mass transfer artifacts between the phases and eventually increasing yields to methyl esters. The use of ethyl acetate as co-solvent increased methyl esters yields up to 31 %.